Functional trait dissimilarity drives both species complementarity and competitive disparity. (29th August 2017) - Wagg, Cameron; Ebeling, Anne; Roscher, Christiane; Ravenek, Janneke; Bachmann, Dörte; Eisenhauer, Nico; Mommer, Liesje; Buchmann, Nina; Hillebrand, Helmut; Schmid, Bernhard; Weisser, Wolfgang W.
Abstract: Niche complementarity and competitive disparity are driving mechanisms behind plant community assembly and productivity. Consequently, there is great interest in predicting species complementarity and their competitive differences from their functional traits as dissimilar species may compete less and result in more complete use of resources. Here we assessed the role of trait dissimilarities for species complementarity and competitive disparities within an experimental gradient of plant species richness and functional trait dissimilarity. Communities were assembled using three pools of grass and forb species based on a priori knowledge of traits related to (1) above‐ and below‐ground spatial differences in resource acquisition, (2) phenological differences or (3) both. Complementarity and competitive disparities were assessed by partitioning the overyielding in mixed species communities into species complementarity and dominance effects. Community overyielding and the underlying complementarity and competitive dominance varied strongly among the three plant species pools. Overyielding and complementarity were greatest among species that were assembled based on their variation in both spatial and phenological traits. Competitive dominance was greatest when species were assembled based on spatial resource acquisition traits alone. In communities that were assembled based on species variation in only spatial or phenological traits, greater competitive dominance was predicted by greater differences in SLA and flowering initiation respectively, while greater complementarity was predicted by greater dissimilarity in leaf area and flowering senescence respectively. Greater differences in leaf area could also be linked to greater species complementarity in communities assembled based on variation in both phenological and spatial traits, but trait dissimilarity was unrelated to competitive dominance in these communities. Our results indicate that complementarity and competitive disparity among species are both driven by trait dissimilarities. However, the identity of the traits that drives the complementarity and competitive disparity depends on the trait variation among species that comprise the community. Moreover, we demonstrate that communities assembled with the greater variation in both spatial and phenological traits show the greatest complementarity among species. A plain language summary is available for this article. Abstract : Plain Language Summary